Improving a Fishing Vessel Monitoring Application During the Covid-19 Pandemic - Sunaryo, Sunaryo (KnE Social Sciences, 2022)
The Covid-19 pandemic has impacted numerous sectors of the economy and society, including the authorities sector. In the government sector, the Covid-19 pandemic has led to changes in the system and work pattern of the State Civil Apparatus (ASN) in carrying out government duties and services to the community. The ASN must offer first-class service to the community, optimally and with integrity. The Directorate General of Surveillance for Marine and Fisheries Resources at the Ministry of Marine Affairs and Fisheries is a state organizer of public services and it has kept improving its public services during the Covid-19 pandemic. An innovation was implemented to improve the monitoring capability of fishing vessels through the SALMON application. Access to fishing vessel monitoring data, which could previously only been done through the website, has developed through the use of Android-based smartphone technology and the addition of call center services. Improving the ability of SALMON during the Covid 19 pandemic has further streamlined technology-based licensing which aims to simplify bureaucratic pathways, streamline government licensing and surveillance of fishing vessels, and create an atmosphere of ‘ease of effort’ for the Indonesian fishing industry. Keywords: SALMON, public service innovation, simplicity in business